U.S. GRAND STRATEGY IN THE EARLY COLD WAR: PRIORITIES, CONCERNS AND POLICY ACTIONS - Javed, Humayun (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2024)
The study aims to identify U.S. concerns and priorities in the immediate post-WWII era while exploring the primary American considerations in formulating a grand strategy during the early Cold War. The paper addresses the question that were Washington’s policy choices during the last stages of the Second World War and early Cold War primarily being driven by Soviet expansion in Eastern Europe. The study is qualitative in nature and uses exploratory research because the existing literature on the early Cold War does not sufficiently explain the rationale for American policymakers to adopt a global role. The research argues that the unmatched extent of U.S. power and influence, along with an ambitious vision to reshape the postwar institutional and security architecture, allowed Washington to formulate a grand strategy for its economic and political footprint in Asia and Europe, where the Soviet Union remained the only standing – yet immensely devastated – victorious power. Moscow’s own traditional insecurities on its western frontier and its considerable strategic influence and vision to shape the political and security landscape in Europe produced U.S.-Soviet tensions as their cooperation due to a common German threat had vanished. Therefore, American leadership was focused on taking global responsibility in the early Cold War to shape postwar international economic and political order in light of the prewar lessons and contain Soviet power and influence from jeopardizing U.S. preeminence on the global stage.